1984
DOI: 10.1159/000145860
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Knee Joint of the Cat

Abstract: Based on dissection of 20 adult specimens the anatomy of the knee joint of the cat is described. An attempt is made to include all functionally relevant structures such as bones, ligaments, menisci, joint capsule and capsular reinforcements. A comparison with the human knee joint is made. There is a high resemblance in construction with the main differences occurring in the proportions of the constituent elements. A comparison of the semimembranosus and biceps femoris receives particular attention. These descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…12 However, our study of cats showed less cartilage differentiation in CCLR and no evidence of either masking of collagen fibres or of lipid droplets or calcification. The macroscopic anatomy of intact CCLs from cats agreed with data reported by others in the current literature; 17,18 the collected findings indicate characteristics of physiological differentiation of fibrocartilage in tendons or ligaments. Moreover, similar results were reported from a study by Heintel of canine tendons.…”
Section: Discussionsupporting
confidence: 87%
“…12 However, our study of cats showed less cartilage differentiation in CCLR and no evidence of either masking of collagen fibres or of lipid droplets or calcification. The macroscopic anatomy of intact CCLs from cats agreed with data reported by others in the current literature; 17,18 the collected findings indicate characteristics of physiological differentiation of fibrocartilage in tendons or ligaments. Moreover, similar results were reported from a study by Heintel of canine tendons.…”
Section: Discussionsupporting
confidence: 87%